(untitled) (Journal of Hama University, 2020)
This research seeks to reveal the role of displacement in the poetry of the poem Aus ibn Hajar’s Ha’eyah . The research began with a brief introduction to the concept of the displacement , then studied the semantic displacement represented in the analogous images and its effect on the characterization of poetry on the verses of the poem then proceeded to analyze a number of rhythmic shifts and feel its effect in the aesthetics of the meanings that the poet wanted to deliver then went on to study the structural shifts that are not surprising in the surprise of the recipient As well as the effect of opening the text on the implications of multiple indications The research concludes with our findings from studying these shifts